2015
DOI: 10.1111/1471-0528.13322
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse and incontinence 15–23 years after first delivery: a cross‐sectional study

Abstract: Objective To study the association between pelvic floor dysfunction (PFD) and mode of delivery and to calculate the risks of PFD comparing caesarean delivery and operative vaginal delivery to normal vaginal delivery 15-23 years after childbirth. A subgroup analysis comparing forceps and vacuum delivery was planned.Design Cross-sectional study.Setting Postal questionnaire.Population 1641 (53%) of 3115 women who delivered their first child in Trondheim, Norway, between January 1990 and December 1997.Methods A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 34 publications
5
38
3
Order By: Relevance
“…Hence potentially increasing use of cesarean section may have beneficial public health consequences from the perspective of pelvic floor health, including decreased need for SUI and pelvic organ prolapse surgery [52], [53]. Our results are consistent with those of a Swedish cohort study that reported vaginal deliveries increased surgical treatment for incontinence (hazard ratio: 2.9; 95% CI, 2.4–3.6) compared with women only having cesarean deliveries.…”
Section: Evidence Synthesissupporting
confidence: 87%
“…Hence potentially increasing use of cesarean section may have beneficial public health consequences from the perspective of pelvic floor health, including decreased need for SUI and pelvic organ prolapse surgery [52], [53]. Our results are consistent with those of a Swedish cohort study that reported vaginal deliveries increased surgical treatment for incontinence (hazard ratio: 2.9; 95% CI, 2.4–3.6) compared with women only having cesarean deliveries.…”
Section: Evidence Synthesissupporting
confidence: 87%
“…Hormonal and mechanical factors affect the female organism during pregnancy, delivery, and the puerperium, causing alterations of the pelvic floor that can lead to PFD . Although these changes tend to regress gradually, with a return to the pre‐pregnancy state in up to 12 months, long‐term follow‐up studies have shown that PFD may persist …”
Section: Introductionmentioning
confidence: 99%
“…This is a secondary analysis of a cross‐sectional study of 608 women with first delivery at Trondheim University Hospital, Norway, between 1 January 1990 and 31 December 1997. The primary aim of this study was to examine differences in PFD and LAM injury after different modes of delivery, and results have been published elsewhere . Women who were still alive and had a postal address in Norway in 2013 were identified from the Hospital Patient Administrative System.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of UI and FI increases with advancing age, but the etiology is believed to be multifactorial . Pregnancy, vaginal delivery, parity, smoking, and body mass index (BMI) are additional risk factors for developing PFD …”
Section: Introductionmentioning
confidence: 99%